Pergeseran Otoritas Pedagogis Guru di Era AI Generatif: Sistematis Literatur Review dalam Perspektif Manajemen Mutu Pendidikan - Masduki Ahmad; Dailami Firdaus; Heni Rochimah; Wulandari Wulandari (CV. Global Cendekia Inti, 2026)
This study examined the shift in teachers' pedagogical authority in the era of generative artificial intelligence (AI) from the perspective of educational quality management. The research was motivated by the increasing use of generative AI by students in learning activities, which not only supports academic tasks but also challenges teachers’ roles, academic integrity, and learning quality. A systematic literature review was conducted using a structured article selection process. Data were collected from 13 reputable scientific articles published between 2023 and 2025 and analyzed through thematic coding. The findings indicate that students primarily use generative AI for academic writing, information retrieval, content comprehension, problem-solving, coding, and multimodal content production. Teachers’ pedagogical authority has shifted from being the main knowledge source to roles including ethical guidance, AI literacy mentorship, information validation, authentic assessment design, collaboration facilitation, and risk management in digital learning. The implications suggest that educational quality in the AI era heavily depends on teachers and institutions managing AI use critically and responsibly. Generative AI can enhance personalized learning, access to information, learning effectiveness, and collaboration; however, without pedagogical oversight, it may increase dependency, weaken cognitive processes, and threaten academic integrity.